Peningkatan Intensitas Tanam Padi Melalui Pemanfaatan Debit Surplus Sungai, Penerapan Sumur Renteng, dan Sistem Giliran - Ahmad Efendi; Donny Harisuseno; Tri Budi Prayogo (Jurnal Irigasi, 2019)
The Irrigation Area of Sumber Pakem has an irrigation service area of 1,151 ha, located in Jember Regency and Bondowoso Regency in the Province of East Java. The existing water supply system in the study area has not been implemented effectively and efficiently. Thus, there are problems in the water distribution during the dry season and fluctuations of water availability between the rainy season and the dry season in Banyubang River. The excess discharge in the rainy season can be stored and used to increase the supply of irrigation in the dry season. Therefore, the purpose of this study is to propose alternative irrigation operational method through the optimization of the surplus discharge of Banyubang River, the application of connected wells, and intensive rotation system. In this study, the proposed method was planned and its impact were evaluated on increased cropping intensity.The result showed that the utilizing of river surplus discharge in the study area can increase rice planting intensity during the Planting Season 1 by 2.03% and Planting Season 2 by 27.28%. The surplus discharge is also utilized to fill the 6,599 connected wells (103 network) with the addition of a discharge intake of 6.00 l/s for 135.33 days. The connected wells is filled during abundant river discharge when the irrigation was carried out continuously so as not to interfere with irrigation water distribution in the study area. Water which is stored in the wells can be used in Planting Season 3 to meet the water needs of tobacco plants covering an area of 467 ha. Thus, rice planting area in this period can be increased to 684 ha. The application of a connected wells and intensive rotation system in the Planting Season 3 can increase rice cropping intensity by 38.02%.